2022
DOI: 10.1109/tste.2022.3171711
|View full text |Cite
|
Sign up to set email alerts
|

Some Fundamental Results for Cyclorotor Wave Energy Converters for Optimum Power Capture

Abstract: Cyclorotor-based wave energy converters (WECs) present a relatively new and innovative paradigm for wave energy harvesting. Their operational principle is based on the generation of lift forces on the rotating hydrofoils due to their interaction with wave-induced circulation of water particles. As a result, relatively little is known about their optimal operation. To date, cyclorotor device performance has been measured by the power of waves radiated by the WEC, while a constant rotational velocity, consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 13 publications
3
10
0
Order By: Relevance
“…The obtained results have confirmed the preliminary results presented in [20], that the control of rotational rate in monochromatic waves can significantly increase increase the generated shaft power P Shaf t . In contrast, active pitch control in monochromatic waves does not significantly increase the shaft power P Shaf t , suggesting the use of an optimal constant pitch angle, for monochromatic waves, especially considering the additional complexity of underwater pitch actuators.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…The obtained results have confirmed the preliminary results presented in [20], that the control of rotational rate in monochromatic waves can significantly increase increase the generated shaft power P Shaf t . In contrast, active pitch control in monochromatic waves does not significantly increase the shaft power P Shaf t , suggesting the use of an optimal constant pitch angle, for monochromatic waves, especially considering the additional complexity of underwater pitch actuators.…”
supporting
confidence: 88%
“…As members of the LiftWEC consortium, the authors derive new optimal pitch and rotational rate control strategies for a cyclorotor with two hydrofoils [17]- [19]. The presented strategies can potentially significantly increase the cyclorotor performance, in terms of the generated shaft power, consistent with some preliminary fundamental results presented in [20].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…where the additional phase offset terms (c i , ĉi ) and (d i , di ) are included beyond (14) and the monochromatic wave frequency ω is replaced with a nominal rotational speed θ0 , which is the optimum (constant) rotational rate for the fundamental period [T 0 , T ], again with the intention of easing the global optimisation problem. T ext , in (15), is an extended time interval selected as twice the interval on which we consider the energy generation [T 0 , T ].…”
Section: Harmonic Control Solutionmentioning
confidence: 99%
“…These pioneering studies focus on wave cancellation as a control performance metric and used a constant cyclorotor rotational speed. More recently, some studies have shown the benefit of a variable rotational velocity, and the use of shaft power as a primary performance metric [14]. Specific studies [15] examined the use of both relatively fast acting (generator torque, foil pitch angles), and slow acting (submergence depth, rotor radius) control actuators have recently emerged, showing potential improvement in power capture of over 100%, Given the disparity of time scales over which control actuators can operate, to date there has been no analysis of the interaction between these different actuator sets on the system performance.…”
Section: Introductionmentioning
confidence: 99%